2009
DOI: 10.2310/jim.0b013e3181adfb5b
|View full text |Cite
|
Sign up to set email alerts
|

DNA Oxidation and Antioxidant Status in Breast Cancer

Abstract: : Data show that serum levels of 8-OHdG and SOD activities are higher in patients with breast cancer. Glutathione peroxidase activity is lower in the breast cancer group. Increased ratio of 8-OHdG/G-Px in breast cancer patients is the evidence for impaired oxidant/ antioxidant balance in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…The role of free radicals, oxidative stress, and lipid peroxidation in carcinogenesis and their contribution to the initiation and progression of the process are well documented (Himmetoglu et al, 2009). In recent years, using MDA as a marker of oxidative stress, there has been a growing interest in studying the role played by lipid peroxidation in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The role of free radicals, oxidative stress, and lipid peroxidation in carcinogenesis and their contribution to the initiation and progression of the process are well documented (Himmetoglu et al, 2009). In recent years, using MDA as a marker of oxidative stress, there has been a growing interest in studying the role played by lipid peroxidation in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that oxidative stress can cause DNA damage followed by an increase in the spontaneous mutation rate, which is a platform for tumor genesis [8][9][10]. 8-Hydroxy-2′-deoxyguanosine (8-OHdG) used as a biomarker for the measurement of endogenous oxidative DNA damage has been found to be significantly higher in various cancers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The oxidative stress, detected by using various biomarkers (including the level of carbonyl groups and 3-nitrotyrosine in proteins, the total antioxidant level (TAS), the activity of antioxidative enzymes), had been observed in breast cancer patients before and during different phases of treatment. [7][8][9][10][11][12][13][16][17][18][19][20][21][22][23] Results of Kedzierska et al 11 have shown that the total level of glutathione (an important physiological antioxidant) in plasma isolated from breast cancer patients (before and during treatment, during different phases of chemotherapy (doxorubicin and cyclophosphamide)) was lower than in healthy persons.…”
Section: Oxidative Stress In Breast Cancermentioning
confidence: 99%